ANALYSIS OF FACTORS THAT INFLUENCE CUSTOMER LOYALTY FOR USING CLOUD KITCHEN IN MEDAN - Tiffany Tiffany; Daniel Cassa Augustinus (Faculty of Economics and Business Universitas Pelita Harapan, 2022)
In this era of the industrial revolution 4.0, innovation and technological development have grown rapidly, especially in the food industry. Due to the pandemic that occurred, the food and beverage business encouraged the development of restaurants with a cloud kitchen model. The concept of this restaurant has begun to be adopted in Indonesia where one of the big companies, Grab Kitchen is using this concept. Within it existence in Medan city, Grab Kitchen (GK) still has minimum perception and still getting negative responses. In answering the problem gap in this research object, researcher examined the relationship between variables such as Service Quality, Customer Perception Value, Customer Satisfaction, and Customer Loyalty. The type of research conducted is descriptive research and casual research. Data analysis will be carried out using quantitative methods by distributing questionnaires to 96 respondents who are consumers of GK Medan. The completed questionnaires were analyzed, and data processed using descriptive statistics, regression analysis and hypothesis testing. From the results of research conducted in analyzing problems at GK Medan, it shows that there is a positive and significant influence of Service Quality, Customer Perception Value, Customer Satisfaction, on Customer Loyalty at GK Medan.BAHASA INDONESIA ABSTRACTDi era revolusi industri 4.0 ini, inovasi dan perkembangan teknologi telah berkembang pesat, khususnya pada industri makanan. Akibat pandemi yang terjadi, bisnis makanan dan minuman mendorong pengembangan restoran dengan model cloud kitchen. Konsep restoran ini sudah mulai diadopsi di Indonesia dimana salah satu perusahaan besar yaitu Grab Kitchen menggunakan konsep ini. Dalam keberadaannya di kota Medan, Grab Kitchen (GK) masih memiliki persepsi yang minimum dan masih mendapat tanggapan negatif. Dalam menjawab gap masalah pada objek penelitian ini, peneliti menguji hubungan antar variabel seperti Kualitas Layanan, Nilai Persepsi Pelanggan, Kepuasan Pelanggan, Loyalitas Pelanggan. Jenis penelitian yang dilakukan adalah penelitian deskriptif dan penelitian kasual. Analisis data akan dilakukan dengan menggunakan metode kuantitatif dengan menyebarkan kuesioner kepada 96 responden yang merupakan konsumen GK Medan. Kuesioner yang lengkap dianalisis, dan data diolah dengan menggunakan statistik deskriptif, analisis regresi dan pengujian hipotesis. Dari hasil penelitian yang dilakukan dalam menganalisis permasalahan di GK Medan menunjukkan bahwa terdapat pengaruh yang positif dan signifikan antara Kualitas Layanan, Nilai Persepsi Pelanggan, Kepuasan Pelanggan, terhadap Loyalitas Pelanggan di GK Medan.